Analysis of environmental sustainability perception in Paraná Basin III residents via Item Response Theory - Bueno, Renan Barufaldi; Silva, Marcelo Andrade; Possan, Edna; Vincenzi, Silvana (Brazilian Journal of Biometrics, 2024)
Environmental sustainability perception encompasses an individual’s ability to process and interpret sensory information related to the environment. This understanding guides them to consciously and actively protect and care for the environment through continuous learning. This article aims to analyze the environmental sustainability perception of residents of the Paraná Basin III using IRT models for polytomous items, relating it to socio-economic and location characteristics. The choice to conduct the research in this Brazilian territory is driven by the hydrographic basin’s substantial influence on the Itaipu hydroelectric power plant and its significance as a crucial water resource for the region. Results showed that: (1) 13.1% of residents have a low perception of sustainability, (2) there were significant differences in perception between cities, with Toledo having the lowest values, and (3) there was a positive relationship between remuneration and perception of sustainability. By analyzing the results presented, it becomes possible to develop effective public policies to improve the region’s perception of sustainability.